Cibaomyces, a new genus of Physalacriaceae from East Asia - Yan-Jia, Hao; Jiao, Qin; Zhu-Liang, Yang (Phytotaxa, 2014)
A new genus in Physalacriaceae, Cibaomyces, typified by C. glutinis, is described using morphological and molecular evidence. Cibaomyces is morphologically characterized by the combination of the following characters: basidioma small to medium-sized, collybioid to tricholomatoid; pileus viscid; hymenophore sinuate to subdecurrent, relatively distant, with brown lamellar edge; stipe sticky and densely covered with felted squamules; basidiospores thin-walled, ornamented with finger-like projections; cystidia nearly cylindrical, thin-walled, often heavily incrusted. Molecular phylogenetic analyses using DNA nucleotide sequences of the internal transcribed spacer region and the large subunit nuclear ribosomal RNA loci indicated that Cibaomyces was related to Gloiocephala, Laccariopsis and Rhizomarasmius. A description, line drawings, phylogenetic placement and comparison with allied taxa are presented. <!–EndFragment–>